Human Resource Management Practice Model of Suvarnaphumi International Airport, Thailand - Duangpaen, Thanida; Choibamroong, Therdchai (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to (1) synthesize the process of human resources management practices of Taiwan Taoyuan International Airport, which is one of the Taiwan’s largest and busiest airport and (2) To suggest the human resources management practices model of Suvarnabhumi International Airport. The purpose of this research to analyze, interpret and summarize the main findings on the human resource management practice model of Suvarnaphumi International Airport in Thailand. Therefore, in-depth interviews, semi-structured interviews are the most common qualitative research techniques were employed as a tool to collect data which helps the researcher to gain the deep information from the respondent and also acknowledge the respondent’s feeling. Finally, in order to developed research questions as the processes of human resources management practices of Taiwan Taoyuan International Airport and what should be the human resources management practices model of Suvarnabhumi International Airport.